PENINGKATAN KINERJA KARYAWAN DITINJAU DARI ASPEK MOTIVASI DAN PENGEMBANGAN KARIR - Abdul Wakil (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
This study aims to describe the effect of motivation and carrier development on employee performance. This study is a qualitative research which is sourced from existing theories and relevant empirical research journals. The results of this study showed that motivation has a positive effect on employee performance and carrier development has a positive effect on employee performance. Keywords: Motivation ; Carrier Development ; Employee Performance